GEOTHERMAL DEVELOPMENT STRATEGIES IN OIL AND GAS COMPANIES - Andwir, Rizaldin; Setiawan, Andri D. (Universitas Sahid, 2023)
Indonesia is a country that has the largest geothermal potential in the world because it is in the ring of fire. Indonesia's geothermal energy reserves are 29,4 GW. However, until 2022, geothermal installed capacity in Indonesia is only around 2,175 GW, which is still far from its true potential. Geothermal energy development is needed for Indonesia to empower sustainable energy systems, so as to achieve the target of 3,1 GW based on the 2017 RUEN. To achieve the RUEN target, better development is needed through the role of the oil and gas industry. Geothermal development is seen as a complex dynamic system, with complex challenges to achieve this goal. This paper aims to understand the complexities of geothermal energy development. For this purpose, this paper analyzes geothermal development with a holistic and systematic approach using the conceptual stage of the system dynamics approach. The conceptual model shows that there are many factors that underlie the development ofgeothermal energy in Indonesia.